Aluminum alloy sheet
Patent Information
- Application Number
- JP2024053566
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2024-03-28
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2044-03-28
AI Technical Summary
【0010】 本発明によれば、アルミニウム合金材の廃材を利用して製造することができ、且つ、曲げ性に優れたアルミニウム合金板材を提供することができる。
Smart Images

Figure 0007933815000004 
Figure 0007933815000001 
Figure 0007933815000002
Abstract
Description
Technical Field
[0001] The present invention relates to an aluminum alloy sheet material used for automobile body panels and the like.
Background Art
[0002] Conventionally, when producing an aluminum alloy, in order to ensure good strength and corrosion resistance, virgin aluminum ingot is used as a casting raw material, and elements such as Si and Mg are added to adjust the chemical composition to a desired range. However, since virgin aluminum ingot consumes a large amount of electric power during production, using virgin aluminum ingot as a casting raw material leads to increased CO2 emissions derived from electric power, which poses a problem of high environmental load. In recent years in particular, as the achievement of carbon neutrality has become a social issue worldwide, the importance of reducing the usage of virgin ingot has been increasing.
[0003] For automobile body panels, 6000-series aluminum alloy sheet materials that are excellent in formability and bake hardening (BH) properties are used. The 6000-series aluminum alloy sheet material has a lower alloy element content than other aluminum alloys and the like, and when reused as a molten aluminum alloy material, the original 6000-series aluminum alloy ingot can be easily obtained, making it also suitable for recycling (for example, Patent Document 1).
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Summary of Invention
Problem to be Solved by the Invention
[0005] However, although Patent Document 1 mentions the improvement of bending workability for 6000-series aluminum alloys, it does not refer to the specific composition and properties of aluminum alloy materials related to recyclability.
[0006] Therefore, there is a need for aluminum alloy materials, such as the 6000 series Al-Mg-Si alloys, that can be manufactured using waste aluminum alloy materials and have excellent bendability and other properties.
[0007] Therefore, the object of the present invention is to provide an aluminum alloy sheet material that can be manufactured using waste aluminum alloy material and has excellent bendability. [Means for solving the problem]
[0008] As a result of diligent research, the inventors have found that, due to the presence of Fe in waste aluminum alloy materials, the proportion of the α-AlFeMnSi phase in the second phase particles of the aluminum alloy decreases, resulting in a decrease in performance (bendability) of the aluminum alloy material produced using it. They have also found that by appropriately adjusting the composition of the aluminum alloy and the manufacturing method to increase the proportion of the α-AlFeMnSi phase in the second phase particles, and by appropriately adjusting the composition of the aluminum alloy to increase its strength, it is possible to obtain an aluminum alloy sheet material with excellent bendability even when using waste aluminum alloy material containing Fe as a raw material.
[0009] In other words, the present invention (1) is, It is an aluminum alloy containing 0.50 to 1.50 mass% Si, 0.35 to 0.80 mass% Mg, 0.08 to 0.60 mass% Fe, 0.001 to 0.40 mass% Cu, 0.01 to 0.25 mass% Mn, and Ti exceeding 0.00 mass% and not exceeding 0.09 mass%; optionally containing one or more elements selected from the group consisting of 0.05 mass% or less Cr, 0.05 mass% or less Zn, and 0.05 mass% or less B, with the remainder being Al and unavoidable impurities. When X-ray diffraction analysis is performed, the ratio of the integral intensity value of the diffraction peak with a peak top around 2θ=42° caused by the α-AlFeMnSi phase (A) to the sum of the integral intensity value of the diffraction peak with a peak top around 2θ=17° caused by the β-AlFeMnSi phase (B) ((A / (A+B))×100) is 10.0% or more. The degree of integration of Cube orientations across the entire thickness of the ND-TD surface must be 10.0 or greater. This is an aluminum alloy sheet material characterized by the following features. Furthermore, the present invention (2) is an aluminum alloy plate material of (1) characterized in that the ratio ((A / (A+B))×100) of the integral intensity value of the diffraction peak having a peak top around 2θ=42° due to the α-AlFeMnSi phase of the second phase particles (A) to the sum of the integral intensity value of the diffraction peak having a peak top around 2θ=17° due to the β-AlFeMnSi phase (B) is 25.0% or more. Furthermore, the present invention (3) is, The tensile strength in the 0°, 45°, and 90° directions relative to the rolling direction is 190 MPa or higher. The elongation in the 0°, 45°, and 90° directions relative to the rolling direction must all be 23% or more. (1) is an aluminum alloy sheet material characterized by the following. [Effects of the Invention]
[0010] According to the present invention, it is possible to provide an aluminum alloy sheet material that can be manufactured using waste aluminum alloy material and has excellent bendability. [Brief explanation of the drawing]
[0011] [Figure 1] This is an X-ray diffraction chart obtained by analyzing an aluminum alloy plate using X-ray diffraction. [Modes for carrying out the invention]
[0012] The aluminum alloy sheet material of the present invention is It is an aluminum alloy containing 0.50 to 1.50 mass% Si, 0.35 to 0.80 mass% Mg, 0.08 to 0.60 mass% Fe, 0.001 to 0.40 mass% Cu, 0.01 to 0.25 mass% Mn, and Ti exceeding 0.00 mass% and not exceeding 0.09 mass%; optionally containing one or more elements selected from the group consisting of 0.05 mass% or less Cr, 0.05 mass% or less Zn, and 0.05 mass% or less B, with the remainder being Al and unavoidable impurities. When X-ray diffraction analysis is performed, the ratio of the integral intensity value of the diffraction peak with a peak top around 2θ=42° caused by the α-AlFeMnSi phase (A) to the sum of the integral intensity value of the diffraction peak with a peak top around 2θ=17° caused by the β-AlFeMnSi phase (B) ((A / (A+B))×100) is 10.0% or more. The degree of integration of Cube orientations across the entire thickness of the ND-TD surface must be 10.0 or greater. This is an aluminum alloy sheet material characterized by the following features.
[0013] The aluminum alloy sheet material of the present invention is made of an aluminum alloy, specifically a 6000 series aluminum alloy material, for example, 0.20 to 0.60 mass% Si, 0.35 mass% or less underThe aluminum alloy can be manufactured using sash scrap containing Fe, Cu in amounts of 0.10 mass% or less, Mn in amounts of 0.10 mass% or less, Mg in amounts of 0.45 to 0.90 mass%, Cr in amounts of 0.10 mass% or less, Zn in amounts of 0.10 mass% or less, and Ti in amounts of 0.10 mass% or less as casting raw materials. Examples of other aluminum alloy waste materials that can be used as casting raw materials for the aluminum alloy sheet material made of the aluminum alloy of the present invention include scrap materials such as offcuts generated during the rolling and slitting processes in the manufacturing of aluminum alloy materials. For scrap of alloys other than the 6000 series that can be used as casting raw materials for the aluminum alloy sheet material made of the aluminum alloy of the present invention, mixed metals extracted from scrapped vehicles or UBC (used beverage can) scrap may be used.
[0014] The aluminum alloy according to the present invention contains Si, Mg, Fe, Cu, Mn, and Ti as essential elements, and may optionally contain Cr, Zn, and B. The aluminum alloy according to the present invention consists of essential elements, optional additives added as needed, and the remainder being aluminum and unavoidable impurities.
[0015] Since Si is a component of aluminum alloy waste, the aluminum alloy of the aluminum alloy sheet material of the present invention contains Si. Si improves strength through the precipitation of Mg-Si intermetallic compounds. The Si content of the aluminum alloy is 0.50 to 1.50 mass%, preferably 0.55 to 1.25 mass%, and more preferably 0.60 to 1.00 mass%. When aluminum alloy waste is used as the raw material for ingots in the manufacture of aluminum alloy sheets, the Fe content in the aluminum alloy sheet material increases, resulting in a lower proportion of the α-AlFeMnSi phase of the second phase. When the proportion of the α-AlFeMnSi phase of the second phase in the aluminum alloy sheet material decreases, the bendability decreases. Therefore, in the aluminum alloy sheet material of the present invention, the Si content is adjusted to the above range. twist, the proportion of the α-AlFeMnSi phase as the second phase is increased. As a result, the aluminum alloy sheet material of the present invention has excellent bendability. In addition, Si contributes to strength improvement. On the other hand, if the Si content of the aluminum alloy is less than the above range, the effect of improving strength cannot be sufficiently obtained. If the content exceeds the above range, coarse Si particles and coarse Mg-Si based intermetallic compounds are formed, leading to deterioration of bending workability.
[0016] Since Mg is contained in the components of aluminum alloy scrap, the aluminum alloy related to the aluminum alloy sheet material of the present invention contains Mg. Mg improves strength through precipitation of Mg-Si based intermetallic compounds. The Mg content of the aluminum alloy is 0.35 to 0.80 mass%, preferably 0.40 to 0.75 mass%, more preferably 0.45 to 0.70 mass%. If the Mg content of the aluminum alloy is less than the above range, the effect of improving strength cannot be sufficiently obtained. If the content exceeds the above range, coarse Mg-Si based intermetallic compounds are formed 、 leading to deterioration of bending workability.
[0017] Since Fe is contained in the components of aluminum alloy scrap, the aluminum alloy related to the aluminum alloy sheet material of the present invention contains Fe. The Fe content of the aluminum alloy is 0.08 to 0.60 mass%, preferably 0.15 to 0.55 mass%, more preferably 0.20 to 0.50 mass%. When scrap of aluminum alloy material is used as the ingot raw material for producing the aluminum alloy sheet material, the Fe content in the aluminum alloy sheet material increases and the proportion of the α-AlFeMnSi phase as the second phase decreases, which lowers the bendability. Therefore, in the aluminum alloy sheet material of the present invention, it is necessary to limit the Fe content in the aluminum alloy to the above range. In addition, Fe contributes to grain refinement. If the Fe content of the aluminum alloy is less than the above range, coarse crystal grains are formed, and surface roughening occurs during forming. If the content exceeds the above range, coarse intermetallic compounds are formed, causing deterioration of bendability.
[0018] Since Cu is contained in the components of aluminum alloy scrap, the aluminum alloy for the aluminum alloy sheet material of the present invention contains Cu. The Cu content of the aluminum alloy is 0.001 to 0.40 mass%, preferably 0.02 to 0.10 mass%, more preferably 0.02 to 0.08 mass%. When aluminum alloy scrap is used as the ingot raw material for producing the aluminum alloy sheet material, the aluminum alloy scrap often contains Cu, and the inclusion of Cu in the aluminum alloy sheet material is unavoidable. However, if the Cu content in the aluminum alloy sheet material is excessively high, the bendability will deteriorate. Therefore, in the aluminum alloy sheet material of the present invention, it is necessary to limit the Cu content in the aluminum alloy to the above range. In addition, Cu contributes to the improvement of strength and formability. If the Cu content of the aluminum alloy is less than the above range, the strength and formability will be insufficient, and if it exceeds the above range, the thread rust resistance will deteriorate.
[0019] The aluminum alloy for the aluminum alloy sheet material of the present invention contains Mn. Mn contributes to the refinement of crystal grains. Mn forms an Al-Mn-Si based intermetallic compound, improves strength through dispersion strengthening, and also forms a solid solution in the aluminum matrix phase to improve strength through solid solution strengthening. The Mn content of the aluminum alloy is 0.01 to 0.25 mass%, preferably 0.02 to 0.20 mass%, more preferably 0.04 to 0.15 mass%. When aluminum alloy scrap is used as the ingot raw material for producing the aluminum alloy sheet material, the aluminum alloy scrap often contains Mn, and the inclusion of Mn in the aluminum alloy sheet material is unavoidable. However, if the Mn content in the aluminum alloy sheet material is excessively high, coarse intermetallic compounds will be formed and cause deterioration of formability. Therefore, in the aluminum alloy sheet material of the present invention, it is necessary to limit the Mn content in the aluminum alloy to the above range. If the Mn content of the aluminum alloy is less than the above range, coarse crystal grains will be formed, and surface roughening will occur during forming. If it exceeds the above range, coarse intermetallic compounds will be formed and cause deterioration of bendability.
[0020] The aluminum alloy sheet material of the present invention contains Ti. Ti provides strength through solid solution strengthening. of It has an improvement effect and a refinement effect on the ingot structure. The Ti content of the aluminum alloy is greater than 0.00 mass% and less than or equal to 0.09 mass%, preferably 0.01 to 0.08 mass%, and more preferably 0.02 to 0.07 mass%. If the Ti content of the aluminum alloy exceeds the above range, coarse intermetallic compounds are formed, which adversely affects the formability.
[0021] The aluminum alloy material of the present invention may contain Cr, Zn, and B as optional additive elements. The content of each of these optional additive elements is 0.05% by mass or less.
[0022] The second phase particles (precipitations) of the aluminum alloy plate material of the present invention include α-AlFeMnSi phase and β-AlFeMnSi phase. In this invention, we focused on the α-AlFeMnSi phase, which has a body-centered cubic structure, and the β-AlFeMnSi phase, which has a monoclinic structure. Whether the second phase particles are α-AlFeMnSi phase or β-AlFeMnSi phase can be analyzed by X-ray diffraction. Figure 1 shows the X-ray diffraction chart when the aluminum alloy material of the present invention is analyzed by X-ray diffraction. In Figure 1, the peak with its peak top around 17° on the horizontal axis 2θ is the diffraction peak caused by the β-AlFeMnSi phase, and the peak with its peak top around 42° on 2θ is the diffraction peak caused by the α-AlFeMnSi phase.
[0023] Furthermore, in the aluminum alloy sheet material of the present invention, when the aluminum alloy according to the aluminum alloy sheet material of the present invention is subjected to X-ray diffraction analysis, the ratio ((A / (A+B))×100) of the integral intensity value of the diffraction peak having a peak top around 2θ=42° due to the α-AlFeMnSi phase (A) and the integral intensity value of the diffraction peak having a peak top around 2θ=17° due to the β-AlFeMnSi phase (B) to the sum of these values is 10.0% or more, preferably 15.0% or more. Hereinafter, the "ratio of the integral intensity value of the diffraction peak with a peak top around 2θ=42° caused by the α-AlFeMnSi phase (A) to the sum of the integral intensity value of the diffraction peak with a peak top around 2θ=17° caused by the α-AlFeMnSi phase (A) and the integral intensity value of the diffraction peak with a peak top around 2θ=17° caused by the β-AlFeMnSi phase (B) ((A / (A+B))×100)" will also be referred to as the "proportion of the α-AlFeMnSi phase in the second phase particles." By ensuring that the proportion of the α-AlFeMnSi phase in the second phase particles is 10.0% or more, preferably 15.0% or more, it is possible to produce an aluminum alloy sheet material that combines recyclability (by utilizing waste aluminum alloy materials) with good bendability. In other words, the aluminum alloy related to the aluminum alloy sheet material of the present invention contains Fe derived from waste aluminum alloy materials, for example, which reduces the proportion of the α-AlFeMnSi phase in the second phase particles of the aluminum alloy forming the aluminum alloy sheet material, thus reducing its performance (bendability). Therefore, in the present invention, by appropriately adjusting the composition of the aluminum alloy and appropriately adjusting the manufacturing method to increase the proportion of the α-AlFeMnSi phase in the second phase particles, it is possible to produce an aluminum alloy sheet material with excellent bendability. In particular, by setting the Si content to 0.50 to 1.50 mass% and the Fe content to 0.08 to 0.60 mass% and the homogenization treatment temperature in manufacturing to 530°C or higher, preferably 540 to 590°C, and more preferably 555 to 590°C, the proportion of the α-AlFeMnSi phase in the second phase particles is increased, resulting in an aluminum alloy sheet material with excellent bendability.
[0024] In the aluminum alloy sheet material of the present invention, when the aluminum alloy according to the aluminum alloy sheet material of the present invention is subjected to X-ray diffraction analysis, the ratio of the integral intensity value of the diffraction peak having a peak top around 2θ=42° due to the α-AlFeMnSi phase (A) to the sum of the integral intensity value of the diffraction peak having a peak top around 2θ=17° due to the β-AlFeMnSi phase (B) ((A / (A+B))×100) of the integral intensity value of the diffraction peak having a peak top around 2θ=42° due to the α-AlFeMnSi phase of the second phase particles (A) is 25.0% or more, which is more preferable in that it is possible to produce an aluminum alloy sheet material that is recyclable, meaning it can be manufactured using waste aluminum alloy materials, and that also possesses strength, toughness, and bendability. By ensuring that the proportion of the α-AlFeMnSi phase in the second phase particles is within the above range, it is possible to produce an aluminum alloy sheet material that combines recyclability (by utilizing waste aluminum alloy materials) with strength, toughness, and bendability. In other words, the aluminum alloy related to the aluminum alloy sheet material of the present invention contains Fe derived from waste aluminum alloy materials, for example, which reduces the proportion of the α-AlFeMnSi phase in the second phase particles of the aluminum alloy forming the aluminum alloy sheet material, thus reducing its performance (toughness and bendability). Therefore, in the present invention, by appropriately adjusting the composition of the aluminum alloy and appropriately adjusting the manufacturing method so that the proportion of the α-AlFeMnSi phase in the second phase particles is within the above range, it is possible to produce an aluminum alloy sheet material with excellent strength, toughness, and bendability. In particular, by setting the Si content to 0.50 to 1.50 mass% and the Fe content to 0.08 to 0.60 mass% and the homogenization treatment temperature in manufacturing to 530°C or higher, preferably 540 to 590°C, and more preferably 555 to 590°C, the proportion of the α-AlFeMnSi phase in the second phase particles is increased, resulting in an aluminum alloy sheet material with excellent strength, toughness, and bendability.
[0025] Furthermore, in the aluminum alloy sheet material of the present invention, when the aluminum alloy according to the aluminum alloy sheet material of the present invention is subjected to X-ray diffraction analysis, the upper limit of the ratio ((A / (A+B))×100) of the integral intensity value of the diffraction peak having a peak top around 2θ=42° due to the α-AlFeMnSi phase to the sum of the integral intensity value (A) of the diffraction peak having a peak top around 2θ=17° due to the α-AlFeMnSi phase of the second phase particles and the integral intensity value (B) of the diffraction peak having a peak top around 2θ=17° due to the β-AlFeMnSi phase is not particularly limited, but for example, 95% or less is a possible value.
[0026] In this invention, the α-AlFeMnSi phase ratio in the second phase particles is measured using a Cu tube X-ray source, manufactured by Rigaku Corporation (product name RINT-2500), under the conditions of 2θ: 10~60°, scan speed: 0.2° / min, integration interval: 0.01°, and measurement surface: plate surface, to obtain X-ray diffraction intensity data. Next, background noise is removed from the obtained X-ray diffraction intensity data. The integral intensity of the diffraction peaks in the range of 2θ = 41.6 to 42.3°, which are attributed to the α-AlFeMnSi phase, is calculated as the integral intensity of the diffraction peak with a peak top around 2θ = 42.1°, which is attributed to the α-AlFeMnSi phase (A). The integral intensity of the diffraction peaks in the range of 2θ = 16.8 to 17.5°, which are attributed to the β-AlFeMnSi phase, is calculated as the integral intensity of the diffraction peak with a peak top around 2θ = 17.2°, which is attributed to the β-AlFeMnSi phase (B). The proportion of the α-AlFeMnSi phase in the second phase particles is then calculated from the obtained integral intensity values.
[0027] The aluminum alloy sheet material of the present invention is rolled in the direction vertical The degree of Cube orientation accumulation in the cross-section, i.e., in the entire thickness of the ND-TD plane, is preferably 10.0 or more, more preferably 15.0 or more. The ND-TD plane refers to the rolling direction. (RD) to It is perpendicular and parallel to the direction normal to the rolling surface (ND) and the direction perpendicular to the rolling surface (TD). The cross-section is such that the degree of Cube orientation is expressed as the ratio to the degree of random orientation of the sample. Having the degree of Cube orientation within the above range enhances recyclability, allowing for manufacturing using waste aluminum alloy, and improves bendability.
[0028] In the present invention, it is more preferable that the density of Cube orientations across the entire thickness of the ND-TD surface of the aluminum alloy sheet material is 20.0 or higher, as this allows for recyclability by enabling production using waste aluminum alloy materials, and enhances the effects of improving strength, toughness, and bendability.
[0029] Furthermore, in the aluminum alloy sheet material of the present invention, the upper limit of the degree of Cube orientation integration over the entire thickness of the ND-TD surface is not particularly limited, but for example, it is 150 or less.
[0030] The aluminum alloy sheet material of the present invention has a tensile strength of 190 MPa or more, preferably 195 MPa or more, and more preferably 200 MPa or more, in the 0°, 45°, and 90° directions relative to the rolling direction. The fact that the tensile strength in all three directions is within the above range, and that the elongation is 23% or more, ensures sufficient formability. If the strength and elongation in at least one of the three directions are low, fracture will occur in the direction with low strength and elongation during forming, and sufficient formability cannot be ensured. Furthermore, having low strength and elongation in at least one direction indicates anisotropy, which leads to a decrease in formability.
[0031] The aluminum alloy sheet material of the present invention has an elongation of 23% or more, preferably 24% or more, and more preferably 25% or more, in the 0°, 45°, and 90° directions relative to the rolling direction. Having the elongation in all three directions within the above range ensures sufficient formability. If the elongation in at least one of the three directions is low, fracture or necking will occur in the direction of low elongation during forming, making it impossible to ensure sufficient formability. Furthermore, having low elongation in at least one direction indicates anisotropy, which leads to a decrease in formability.
[0032] The aluminum alloy sheet material of the present invention is used in automobile body panels, hoods, doors, fenders, etc.
[0033] Because the aluminum alloy sheet material of the present invention has high upper limits for components such as Fe and Cu, it is easy to reuse as part of the casting raw material when it becomes waste material, and is therefore suitably used as a casting raw material in the following method for manufacturing the aluminum alloy sheet material of the present invention.
[0034] The aluminum alloy sheet material of the present invention is, for example, Using a casting raw material containing waste aluminum alloy material, an aluminum alloy ingot is cast containing 0.50 to 1.50 mass% Si, 0.35 to 0.80 mass% Mg, 0.08 to 0.60 mass% Fe, 0.001 to 0.40 mass% Cu, 0.01 to 0.25 mass% Mn, and Ti exceeding 0.00 mass% and not exceeding 0.09 mass%; optionally containing one or more elements selected from the group consisting of 0.05 mass% or less Cr, 0.05 mass% or less Zn, and 0.05 mass% or less B, with the remainder being Al and unavoidable impurities. The aforementioned aluminum alloy ingot is subjected to a homogenization treatment by heating it to 530°C or higher. The homogenized material is then hot-rolled at 300-580°C. The hot-rolled material is cold-rolled, and if necessary, intermediate annealing is performed before cold rolling or between cold-rolling passes. The aforementioned cold-rolled material can be manufactured by solution treatment at 500-600°C, followed by a pre-aging treatment.
[0035] In other words, the method for manufacturing aluminum alloy sheet material according to the present invention is Using a casting raw material containing waste aluminum alloy material, an aluminum alloy ingot is cast containing 0.50 to 1.50 mass% Si, 0.35 to 0.80 mass% Mg, 0.08 to 0.60 mass% Fe, 0.001 to 0.40 mass% Cu, 0.01 to 0.25 mass% Mn, and Ti exceeding 0.00 mass% and not exceeding 0.09 mass%; optionally containing one or more elements selected from the group consisting of 0.05 mass% or less Cr, 0.05 mass% or less Zn, and 0.05 mass% or less B, with the remainder being Al and unavoidable impurities. The aforementioned aluminum alloy ingot is subjected to a homogenization treatment by heating it to 530°C or higher. The homogenized material is then hot-rolled at 300-580°C. The hot-rolled material is then cold-rolled, and if necessary, before cold rolling or between cold-rolling passes. in Intermediate annealing, The cold-rolled material is melted at 500-600°C. bodyThis is a method for manufacturing aluminum alloy sheet material, characterized by chemical treatment followed by a preliminary aging treatment.
[0036] In the present invention's method for manufacturing aluminum alloy sheets, first, an aluminum alloy ingot is cast using a casting raw material containing waste aluminum alloy material, preferably using a casting raw material in which the proportion of waste aluminum alloy material used is 10% by mass or more, more preferably 30% by mass or more, to cast the aluminum alloy ingot. In other words, in the present invention's method for manufacturing aluminum alloy sheets, waste aluminum alloy material is used as part of the casting raw material. By having the proportion of waste aluminum alloy material used in the casting raw material within the above range, it is possible to obtain an aluminum alloy sheet with excellent recyclability and bendability, preferably an aluminum alloy sheet with excellent recyclability and strength, toughness, and bendability.
[0037] In the casting method for manufacturing aluminum alloy sheets of the present invention, the waste material of the aluminum alloy material used as the casting raw material is an aluminum alloy material containing Mg, for example, waste material of Al-Mg-Si aluminum alloy material such as 6000 series aluminum alloy material, specifically 6000 series aluminum alloy material, for example, 0.20 to 0.60 mass% Si, 0.35 mass% or less under Examples of aluminum alloy waste include window frame scraps containing elements such as Fe, Cu (less than 0.10 mass%), Mn (less than 0.10 mass%), Mg (0.45 to 0.90 mass%), Cr (less than 0.10 mass%), Zn (less than 0.10 mass%), and Ti (less than 0.10 mass%). Examples of aluminum alloy waste include scraps generated during the rolling and slitting processes in the manufacturing of aluminum alloys, body panels from scrapped or unused automobiles, and mixed metals and UBC (used beverage can) scraps extracted from scrapped vehicles.
[0038] In the casting method for manufacturing aluminum alloy sheets of the present invention, the average content of each chemical component in the waste aluminum alloy material used as the casting raw material (the ratio of the total amount of each chemical component contained in the waste aluminum alloy material to the total mass of the waste aluminum alloy material used in casting) may be, for example, the following: Si content of 0.20 to 0.60 mass%, Mg content of 0.45 to 0.90 mass%, Fe content of 0.35 mass% or less, Cu content of 0.10 mass% or less, Mn content of 0.10 mass% or less, Ti content of 0.10 mass% or less, Zn content of 0.10 mass% or less, and Cr content of 0.10 mass% or less. Furthermore, the waste aluminum alloy material used as the casting raw material may contain unavoidable impurities.
[0039] In the method for manufacturing aluminum alloy sheet material of the present invention, casting is performed to produce 0.50 to 1.50 mass%, preferably 0.55 to 1.25 mass%, more preferably 0.60 to 1.00 mass% of Si and 0.35 to 0.80 mass % Preferably 0.45 to 0.75% by mass, more preferably 0.50 to 0.70% by mass % Mg, 0.08-0.60 mass%, preferably 0.15-0.55 mass%, more preferably 0.20-0.50 mass%, Fe, 0.001-0.40 mass%, preferably 0.01-0.30 mass%, more preferably 0.02-0.20 mass%, more preferably 0.02-0.10 mass%, more preferably 0.02-0.08 mass%, Cu, 0.01-0.25 mass%, preferably 0.02-0.20 mass%, A more preferably 0.04 to 0.15 mass% of Mn and more than 0.00 mass% to 0.09 mass% preferably 0.01 to 0.08 mass%, more preferably 0.02 to 0.07 mass% of Ti are contained, and optionally one or more elements selected from the group consisting of 0.05 mass% or less of Cr, 0.05 mass% or less of Zn, and 0.05 mass% or less of B, with the remainder being Al and unavoidable impurities, to be produced as an aluminum alloy ingot.
[0040] The casting method in the method for manufacturing aluminum alloy sheets of the present invention is not particularly limited, and ordinary casting methods and casting conditions can be appropriately selected.
[0041] In the present invention's method for manufacturing aluminum alloy sheets, the aluminum alloy ingot is then subjected to a homogenization treatment by heating it at 530°C or higher, preferably 540-590°C, and more preferably 555-590°C, to obtain a homogenized product. The homogenization treatment temperature affects the ratio of α-AlFeMnSi phase to β-AlFeMnSi phase in the second phase particles of the aluminum alloy in the aluminum alloy sheet. By keeping the homogenization treatment temperature within the above range, the ratio of the α-AlFeMnSi phase can be increased. In the method for manufacturing aluminum alloy sheets of the present invention, by setting the chemical composition of the aluminum alloy ingot subjected to homogenization treatment within the above range and setting the homogenization treatment temperature within the above range, the ratio of the integral intensity value of the diffraction peak having a peak top at 2θ=42° due to the α-AlFeMnSi phase (A) to the sum of the integral intensity value of the diffraction peak having a peak top at 2θ=17° due to the β-AlFeMnSi phase (B) ((A / (A+B)) × 100) (proportion of α-AlFeMnSi phase in the second phase particles) can be set to 10.0% or more, preferably 20.0% or more, and more preferably 25.0%. This makes it possible to obtain an aluminum alloy sheet that is recyclable, can be manufactured using waste aluminum alloy, and has good bendability, and preferably also has good strength and toughness. The homogenization treatment time is appropriately selected to obtain the effects of the present invention, but is preferably 3 hours or more, more preferably 6 hours or more.
[0042] In the present invention's method for manufacturing aluminum alloy sheets, the homogenized material is then hot-rolled at 300-580°C to obtain a hot-rolled product. The reduction ratio in hot rolling is preferably 95% or more. The reduction ratio in hot rolling is given by the following formula: Hot rolling reduction ratio (%) = ((thickness of sheet before hot rolling - thickness of sheet after hot rolling) / thickness before hot rolling) × 100 It can be calculated using this method.
[0043] In the method for manufacturing aluminum alloy sheet material of the present invention, the hot-rolled material is then cold-rolled to obtain a cold-rolled material. Cold rolling may be performed in a single pass, or two or more passes may be performed. If two or more passes are performed, intermediate annealing may be carried out between passes by heating at 250-550°C, preferably 300-500°C, for 0.5 hours or more. The total reduction ratio in cold rolling is 50% or more, preferably 60% or more. The total reduction ratio in cold rolling is given by the following formula: Total reduction ratio (%) for cold rolling = ((Initial of (Thickness of the sheet before cold rolling of the first pass - Thickness of the sheet after cold rolling of the last pass) / (Thickness of the sheet before cold rolling of the first pass) × 100 It can be calculated using this method.
[0044] In the present invention's method for manufacturing aluminum alloy sheets, the cold-rolled material is then subjected to a solution treatment, where it is held at 500-600°C, preferably 520-580°C, for 2-30 seconds, preferably 5-25 seconds. In the solution treatment, the cold-rolled material is held at the above temperature range for the above holding time, and then cooled at a rate of 1°C / second or more. Next, the solution-treated material obtained from the solution treatment is subjected to a pre-aging treatment at 30-150°C, preferably 50-130°C, to obtain an aluminum alloy sheet.
[0045] In this way, the method for manufacturing aluminum alloy sheets of the present invention uses waste aluminum alloy material as part of the casting raw material to obtain the aluminum alloy sheet of the present invention.
[0046] The present invention will be specifically described below with reference to examples, but the present invention is not limited to the examples shown below. [Examples]
[0047] An aluminum alloy having the alloy composition shown in Table 1 was cast by DC casting. The ultimate temperature of the homogenization treatment shown in Table 2 was set as the target temperature, and the time from reaching the target temperature minus 5°C to the end of heating was defined as the holding time. After the homogenization treatment was completed, hot rolling, cold rolling, appropriate intermediate annealing, solution treatment and pre-aging treatment were performed to obtain an aluminum alloy sheet material with a sheet thickness of 1 mm. Using the obtained alloy sheet material, the proportion of the α-AlFeMnSi phase in the second-phase particles and the integration degree of the Cube orientation were measured. Through the aging treatment, the proof stress in the 0°, 45°, and 90° directions was increased to the values shown in Table 3, and the bendability was evaluated.
[0048] <X-ray diffraction analysis> Using a Cu tube as the X-ray source, measurement was performed under the conditions of 2θ: 10 to 60°, scanning speed: 0.2° / min, integration interval: 0.01°, measurement surface: sheet surface, using a device manufactured by Rigaku Corporation (trade name RINT-2500), to obtain X-ray diffraction intensity data. Next, the background was removed from the obtained X-ray diffraction intensity data, the integrated intensity value of the diffraction peak in the range of 2θ=41.6 to 42.3° attributed to the α-AlFeMnSi phase was determined as the integrated intensity value (A) of the diffraction peak having a peak top near 2θ=42° attributed to the α-AlFeMnSi phase, and the integrated intensity value of the diffraction peak in the range of 2θ=16.8 to 17.5° attributed to the β-AlFeMnSi phase was determined as the integrated intensity value (B) of the diffraction peak having a peak top near 2θ=17° attributed to the β-AlFeMnSi phase. Then, the value of (A / (A+B))×100 was calculated.
[0049] <Measurement methods for tensile strength, proof stress, elongation, and n-value> A No. 5 test piece specified in JIS Z2241 is sampled from the test material such that the longitudinal direction is parallel to the rolling direction. Using this test piece, a tensile test is performed by a method in conformity with JIS Z2241, so as to calculate the tensile strength, 0.2% proof stress and elongation in the direction parallel to the rolling direction (0° direction). Further, a No. 5 test piece with an angle of 45° between the longitudinal direction and the rolling direction and a test piece with the longitudinal direction perpendicular to the rolling direction are sampled from the test material, and a tensile test is performed by a method conforming to JIS Z2241 in the same manner as described above, thereby calculating the tensile strength, 0.2% proof stress and elongation in the direction inclined by 45° with respect to the rolling direction (45° direction) and the direction perpendicular to the rolling direction (90° direction).
[0050] <Method for Measuring Integration Degree of Cube Orientation> For the integration degree of the Cube orientation, using an X-ray diffractometer (RINT-2000 manufactured by Rigaku Corporation), incomplete pole figures of the (111) plane, (220) plane, and (200) plane were measured by the Schulz reflection method, which is one of the X-ray diffraction measurement methods, in the range of an inclination angle of 15 to 90°, to acquire orientation information of the texture. Then, from the obtained orientation information of the texture, the Cube integration degree was determined using pole figure analysis software. The integration degree is represented by the ratio between the integration degree of the Cube orientation and the integration degree of a sample having a random orientation, and is denoted as a random ratio. The measurement surface was defined as the ND-TD plane.
[0051] <Hemming Test> After 10% tensile pre-strain, a 180° bending test was performed at an inner bending radius of 0.5 mm, and then a hemming test was performed using a middle plate having a plate thickness of 0.9 mm. The surface of the bent outer peripheral portion after the test was scored in accordance with the judgment criteria of JIS H7701. A score of 2 or less was regarded as acceptable, and a score of 3 or more was regarded as unacceptable.
[0052] [Table 1]
[0053] [Table 2]
[0054] [Table 3]
[0055] In Table 3, the integral ratio α (%) is the ratio ((A / (A+B)) × 100) of the integral intensity of the diffraction peak with a peak top around 2θ=42° caused by the α-AlFeMnSi phase (A) and the integral intensity of the diffraction peak with a peak top around 2θ=17° caused by the β-AlFeMnSi phase (B) to the sum of these integral intensity values (A / (A+B)) when X-ray diffraction analysis is performed.
[0056] Based on the above results, the aluminum alloy sheets used in the inventive examples, Tests No. 1-3 and 5-8, exhibit excellent bendability. Furthermore, the aluminum alloy sheets used in the inventive examples, Tests No. 1-3 and 5-8, exhibit excellent strength, toughness, and bendability. The average chemical composition of waste 6000 series aluminum alloy materials is typically as follows: Si content of 0.20-0.60 mass%, Mg content of 0.45-0.90 mass%, Fe content of 0.35 mass% or less, Cu content of 0.10 mass% or less, Mn content of 0.10 mass% or less, Ti content of 0.10 mass% or less, Zn content of 0.10 mass% or less, and Cr content of 0.10 mass% or less. As a result, from the chemical composition of the aluminum alloy sheets of Tests No. 1-3 and 5-8, it was found that up to 99% by mass of waste 6000 series aluminum alloy material can be used in the casting raw material for their manufacture, and that aluminum alloy sheets with excellent bendability, preferably aluminum alloy sheets with excellent strength, toughness, and bendability, can be manufactured using waste 6000 series aluminum alloy material.
Claims
1. It is an aluminum alloy containing 0.50 to 1.50 mass% Si, 0.35 to 0.80 mass% Mg, 0.08 to 0.60 mass% Fe, 0.001 to 0.40 mass% Cu, 0.01 to 0.25 mass% Mn, and Ti exceeding 0.00 mass% and not exceeding 0.09 mass%; optionally containing one or more elements selected from the group consisting of 0.05 mass% or less Cr, 0.05 mass% or less Zn, and 0.05 mass% or less B, with the remainder being Al and unavoidable impurities. When X-ray diffraction analysis is performed, the ratio of the integral intensity value of the diffraction peak with a peak top around 2θ = 42° caused by the α-AlFeMnSi phase (A) to the sum of the integral intensity value of the diffraction peak with a peak top around 2θ = 17° caused by the β-AlFeMnSi phase (B) ((A / (A+B)) × 100) is 10.0% or more. The degree of accumulation of cube orientations across the entire thickness of the ND-TD plane, which is perpendicular to the rolling direction (RD) and parallel to the direction normal to the rolling surface (ND) and the direction perpendicular to the rolling direction (TD), is 10.0 or greater. An aluminum alloy sheet material characterized by the following features.
2. The aluminum alloy sheet material according to claim 1, characterized in that the ratio of the integral intensity value of the diffraction peak having a peak top around 2θ = 42° due to the α-AlFeMnSi phase (A) to the sum of the integral intensity value of the diffraction peak having a peak top around 2θ = 17° due to the β-AlFeMnSi phase (B) ((A / (A+B)) × 100) is 25.0% or more.
3. The tensile strength in the 0°, 45°, and 90° directions relative to the rolling direction is 190 MPa or more. The elongation in the 0°, 45°, and 90° directions relative to the rolling direction must all be 23% or more. The aluminum alloy sheet material according to claim 1, characterized by the above.
Citation Information
Patent Citations
Aluminum alloy sheet having excellent bending workability and production method thereof
JP2003226926A
Aluminum alloy sheet having excellent bending workability and hardenability in coating / Baking, and production method thereof
JP2003277870A
Al-Mg-Si-BASED ALUMINUM ALLOY SHEET SUPERIOR IN BENDABILITY
JP2010116594A
Al-Mg-Si-BASED ALUMINUM ALLOY SHEET FOR AUTOMOBILE PANEL AND MANUFACTURING METHOD THEREFOR
JP2015067857A
Aluminum alloy sheet excellent in ridging resistance and hem bendability and manufacturing method therefor
JP2017061709A